Subclinical motor impairment assessed with an engineered glove correlates with magnetic resonance imaging tissue damage in radiologically isolated syndrome. (24th September 2018) - Bonzano, L.; Bove, M.; Sormani, M. P.; Stromillo, M. L.; Giorgio, A.; Amato, M. P.; Tacchino, A.; Mancardi, G. L.; De Stefano, N.
Abstract : Background: An engineered glove measuring finger motor performance previously showed ability to discriminate early‐stage multiple sclerosis (MS) patients from healthy controls (HCs). Radiologically isolated syndrome (RIS) classifies asymptomatic subjects with brain magnetic resonance imaging (MRI) abnormalities suggestive of multiple sclerosis. Methods: Seventeen asymptomatic subjects with RIS and 17 HCs were assessed. They performed finger‐to‐thumb opposition sequences at their maximal velocity, metronome‐paced bimanual movements and conventional and diffusion tensor MRI. Results: Subjects with RIS showed lower ( P = 0.005) maximal velocity and higher ( P = 0.006) bimanual coordination impairment than HCs. In RIS, bimanual coordination correlated with T2‐lesion volume, fractional anisotropy and radial diffusivity in the white matter. Conclusions: These findings point out the relevance of fine hand measures as a robust marker of subclinical disability.